A Validated HPLC Method for the Determination of Eriocalyxin B in Plasma and its Application to Pharmacokinetic Studies - Wang, Z.; Yuan, Q.; Sun, J-h.; Cui, Z.; Chen, H-y.; Wu, H.; Chen, J-x. (Arzneimittelforschung, 2012)
The purpose of this study was to determine EriB in plasma by using the method of HPLC and collect the preclinical pharmacokinetic parameters of EriB.The analysis involved a simple liquid-liquid extraction. After making alkaline with NaOH, plasma was extracted with diethyl ether and the organic extract was then evaporated. From there, the residue was reconstituted in to the mobile phase. Chromatographic separation was achieved on the C18 column using acetonitrile and 0.1% triethylamine as mobile phase delivered at 1.0 ml/min. The UV detector wavelength was set at 233 nm. Standard curves were linear over the concentration range of 50–2 500 ng/ml.The mean predicted concentrations of the quality control (QC) samples deviated by less than 3% from the corresponding nominal values; the intra-assay and inter-assay precision of the assay were within 10% relative standard deviation. The extraction recovery of EriB was more than 80%.The developed method has been applied to the pharmacokinetic study of EriB in rats.
Keywords: biopharmaceuticals; gastrointestinal pharmacology; pharmacokinetic